2022
DOI: 10.21462/jeltl.v7i1.751
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Language Teaching and Its Implementation in Online Learning: The Teachers’ Voice

Abstract: <p><em>Communicative Language Teaching has been popular as a pedagogical approach in teaching L2 that may help students gain communicative competence. This research aimed to investigate teachers' perceptions of CLT and its implementation in online learning. This research adopted a survey research design, and 30 teachers were involved as the participants. The participants were from junior high school and senior high school teachers in Tanjungpinang-Bintan and Batam. Two questionnaires were used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…It is necessary to explore distinct pedagogical approaches that have gained recognition and adoption in language education. For example, Gloriez (2022) concluded that communicative language teaching (CLT) fosters interactive communication and the practical application of language skills, aligning well with the requirements of virtual engagement. Task-based language teaching (TBLT) emphasizes practical language acquisition through problem-solving (Chen & Wang, 2019).…”
Section: Pedagogical Approaches In English Language Learningmentioning
confidence: 99%
“…It is necessary to explore distinct pedagogical approaches that have gained recognition and adoption in language education. For example, Gloriez (2022) concluded that communicative language teaching (CLT) fosters interactive communication and the practical application of language skills, aligning well with the requirements of virtual engagement. Task-based language teaching (TBLT) emphasizes practical language acquisition through problem-solving (Chen & Wang, 2019).…”
Section: Pedagogical Approaches In English Language Learningmentioning
confidence: 99%
“…Pembelajaran sangat penting harus tetap berjalan meskipun sekarang dunia sedang krisis sebab adanya suatu wabah Covid yang dapat menggangu kesehatan manusia. Penyebaran Covid-19 yang semakin meluas telah mengubah sistem pendidikan (Ahmadi & Ilmiani, 2020;Amiruddin & Jannah, 2021;Ariyanti, 2020;Cahyadi, 2020;Erliza & Septianingsih, 2022;Hermansyah & Aridah, 2021;Hsu et al, 2022), dari pembelajaran secara langsung tatap muka di kelas menjadi pembelajaran secara jarak jauh dari rumah (Alabdulaziz & Tayfour, 2023;Al-Jarf, 2022;Azhari & Fajri, 2022) dan menjadi pembelajaran yang berbasis online (Darmawansah & Indartono, 2019;Fitriyah & Jannah, 2021;Gloriez, 2022;Haniah et al, 2021;Putra, 2021). Demi mengutamakan keselamatan dan kesehatan pendidik, tenaga kependidikan, peserta didik, keluarga, dan masyarakat secara umum, serta mempertimbangkan tumbuh kembang peserta didik dalam upaya pemenuhan layanan pendidikan selama pandemi Covid-19.…”
Section: A Pendahuluanunclassified
“…Jenis penelitian yang digunakan ialah deskriptif kualitatif. Deskriptif adalah suatu metode penelitian yang ditujukan untuk menggambarkan fenomena-fenomena yang ada, yang berlangsung saat ini atau saat lampau (Fitrah & Luthfiyah, 2017). Fokus penelitian pada penelitian ini yaitu penerapan pembelajaran jarak jauh yang dilakukan oleh guru di MI Ar-Rahmah Samarinda selama masa pandemi covid-19.…”
Section: Metode Penelitianunclassified
See 1 more Smart Citation